Implementasi Supervisi Akademik Kepala Madrasah dalam Peningkatan Kompetensi Profesional Guru Al-Qur’an Hadis di Madrasah Tsanawiyah - Diniah Diniah; Rohimin Rohimin; Adisel Adisel; Ramdelon Ramdelon (Journal Of Administration and Educational Management (ALIGNMENT), 2026)
This study aims to analyze the implementation of academic supervision by madrasah principals in improving the professional competence of Al-Qur'an and Hadith teachers in junior high schools (Madrasah Tsanawiyah) throughout Bengkulu City. The research employed a mixed methods approach with a predominantly qualitative design, involving 30 informants consisting of madrasah principals, teachers, supervisors, and administrators of the KKMTs (School of Islamic Studies) and MGMP (School of Islamic Studies). Data were collected through observation, interviews, documentation, and questionnaires, and analyzed using thematic and descriptive analysis. The results indicate that academic supervision has been implemented according to formal stages, including planning, implementation, and follow-up. However, it remains predominantly administrative in nature. Supervision implementation demonstrates that teachers have met minimum standards for material mastery but are limited in innovative methods and contextualization of learning. Supervision follow-up has not been conducted systematically and sustainably. The study concludes that academic supervision makes a positive contribution to increasing teachers' reflective awareness and professional competence. However, it requires strengthening needs-based planning, improving the supervisory competence of madrasah principals, and developing a structured follow-up system to be more effective and sustainable.   Keywords: Academic Supervision, Madrasah Principal, Professional Competence, Al-Qur'an Teacher